2010
DOI: 10.1111/j.1471-0528.2010.02529.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐ versus double‐layer hysterotomy closure at primary caesarean delivery and bladder adhesions

Abstract: Objective To determine the association between single-layer (one running suture) and double-layer (second layer or imbricating suture) hysterotomy closure at primary caesarean delivery and subsequent adhesion formation.Design A secondary analysis from a prospective cohort study of women undergoing first repeat caesarean section.Setting Department of Obstetrics and Gynecology, Stanford University, Stanford, CA, USA.Population One hundred and twenty-seven pregnant women undergoing first repeat caesarean section.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…4 In a study, 38 of 7725 (0.49%) women who received LAVH suffered urinary tract injury (30 with bladder injury, 8 with ureteral injury). The investigators also reported that the possibility of bladder injury was higher in cases with a history of cesarean section and anterior colpotomy.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a study, 38 of 7725 (0.49%) women who received LAVH suffered urinary tract injury (30 with bladder injury, 8 with ureteral injury). The investigators also reported that the possibility of bladder injury was higher in cases with a history of cesarean section and anterior colpotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding urologic injury, the choice of closing the hysterotomy with single- versus double-layer may also be a factor in the future prevention of bladder injury. When controlling for confounders, single-layer hysterotomy closure has been found to have a nearly sevenfold increase in the odds of developing bladder adhesions when compared with double-layer closure [34]. …”
Section: Preventionmentioning
confidence: 99%
“…Double-layer closure likely reduces the exposure of raw surgical surfaces, which can lead to fibrosis and adhesion formation [34]. There are no studies that comment specifically on the type of hysterotomy closure relating to bladder injury.…”
Section: Preventionmentioning
confidence: 99%
“…Risk factors include intraperitoneal bleeding, infection, tissue ischemia, chemical irritation and excessive organ manipulation. Careful hemostasis and tissue manipulation, minimization of ischemia, closure of the parietal peritoneum [ [20] , [22] , [23] , [24] ] and a double-layer closure hysterotomy [ 25 ] help to prevent or reduce the formation of adhesions.…”
Section: Complications Related To Prior Uterine Scarsmentioning
confidence: 99%